Development and validation of a tool to assess the organizational consequences of occupational stress among secondary school teachers in Sri Lanka - Buddhini Denuwara; Nalika Gunawardena; Madhubhashinee Dayabandara; Dulani Samaranayake (College of Community Physicians of Sri Lanka, 2023)
Introduction: Literature revealed the lack of a comprehensive tool to assess organizational consequences of occupational stress (OCOS) among schoolteachers. Objectives: To develop and validate an instrument to measure the OCOS among secondary school teachers in Sinhala medium government schools (OCOST-Sinhala) Methods: Triangulation of quantitative and qualitative methods was used to design and validate OCOST-Sinhala. Item generation was guided by a conceptual framework. Reducing the items was through an assessment of a panel of experts and by Principal Component Analysis (PCA). PCA was performed among 360 secondary teachers to assess the factor structure. Construct validity was assessed by Confirmatory Factor Analysis (CFA) and a multi-trait scaling analysis in a survey among 300 secondary teachers. Cronbach' alpha and test re-test reliability were determined. Results: OCOST-Sinhala had 45 items in seven domains (self-efficacy, work engagement, motivation, job satisfaction, enthusiasm, workload & work performance). In PCA, 65.98% of the variance was explained. All the indices used to evaluate the fitness of the model, confirmed that the statistical fitness of the original seven factors model provide valid results. CFA and multi-trait scaling analysis confirmed the construct validity with reliability confirmed as good (Cronbach's alpha 0.92; test re-test reliability >0.7). Conclusions & Recommendations: The developed OCOST-Sinhala was found to be a valid and reliable test to assess OCOS among secondary school teachers in Sri Lanka.